Factors Associated with the Use of Solar Energy in Urban Households - Case Study: Municipality of São José Dos Campos - Garcia, Lucas B.; Alves Fiore, Fabiana; Carvalho , Fernando L. C. (International Journal of Energy Economics and Policy, 2023)
The increased demand for electricity and greenhouse gas emissions resulting from the current energy matrix reinforces the need to expand the use of renewable energy. The conversion of solar energy into electrical energy is the fastest growing worldwide and Brazil has a potential greater than that of developed countries that use it on a large scale. However, it is observed that decentralized generation with the use of photovoltaic panels, in households, occurs at a slower pace than in other countries. We studied a case of the municipality of São José dos Campos, a city with a high human development index in the state of São Paulo, seeking to understand the relevant factors that affect the expansion of installation and use of solar energy. We developed the case study from the collection of information with actors in the process, namely, the government and residents of four neighborhoods in the city. Among the research results, the importance of public guidance for the expansion of the use of technology stand out; the recognition of the use of solar energy, especially in neighborhoods where there are already similar facilities and in those with high purchasing power. It was also found that cultural barriers to the appropriation of technology can be overcome by referential learning and by raising the awareness of the population on environmental issues.